The worst passions of human nature : White supremacy in the Civil War north - Escott, Paul D., 1947- (Nation divided., 2020)
"This book examines the contrast between progress on emancipation and the persistence of virulent racism and white supremacist attitudes in the Civil War North. It analyzes both northern politics and the racial attitudes and assumptions that were revealed in newspapers, books, and magazines. Its central arguments are about the Democratic Party, the Republican Party, and the racism that flourished in Northern society and culture"--